Unconventional reduction in resistivity of atomic scale topological semimetal of NbP and TaP - Kim, Yea-Ji; Song, Youngmin; Lim, Dong-Hyun; Oh, Il-Kwon (Proceedings of the IEEE International Interconnect Technology Conference, 2025)
Topological semimetals (TSMs), particularly NbP and TaP, are attracting increasing attention as promising candidates for next-generation interconnect materials owing to their exceptional low-dimensional transport characteristics. In contrast to conventional metals that exhibit significant resistivity increases at the nanoscale, both NbP and TaP demonstrate an unconventional reduction in resistivity when scaled down to atomic thicknesses. This anomalous behavior is attributed to topologically protected surface states and the presence of Weyl nodes, which enable robust, low-resistance conduction channels. Experimental studies on high-quality single-crystalline NbP nanobelts and ultra-thin NbP films have revealed room-temperature resistivity values significantly lower than bulk NbP and even conventional metals of similar dimensions. Similarly, chemically synthesized TaP single crystals exhibit strong Weyl semimetal characteristics with metallic behavior and favorable residual resistivity ratios. These findings confirm the potential of NbP and TaP as key materials for ultrathin, high-performance interconnects, paving the way for next-generation nanoelectronic and spintronic systems. To fully realize this potential, future research must address key challenges including the reproducible synthesis of atomically thin films, the preservation of topological properties under extreme dimensional scaling, and the controlled integration of these materials into hybrid quantum systems. Continued advances in deposition techniques and interface engineering will be critical to the practical realization of TSM-based device architectures.